USO DO MODELO DE ALOCAÇÃO DE BANDA GENERALIZADO (G-BAM) EM CONFORMIDADE COM A NEUTRALIDADE DE REDE - PROPOSTA E AVALIAÇÃO - BARRETO, David Santana e Silva (2017)
The flow of data across the Internet has grown considerably in the last years and maintains this trend in volume, complexity and variety, and therefore needs to be adequately managed by ISPs. Network neutrality represents the concept that Internet traffic in general should not be discriminated by ISPs based on its source, destination and content. To achieve this goal, a number of countries adopt a hard stance and prohibit certain abusive conducts. An open issue and challenging task is to propose an operational and effective traffic management model that can implement and comply with the concept of network neutrality on ISPs networks. This dissertation presents evidence on the use of Bandwidth Allocation Models (BAMs) as a mechanism to implement neutrality in IP/MPLS networks. BAMs, in brief, can allocate resources on demand and have distinct “behaviors” that can be exploited to achieve network neutrality. This work introduces the AllocTC-Sharing behavior reproduced by the Generalized Bandwidth Allocation Model (G-BAM), discusses how this behavior can achieve a network operation in accordance with network neutrality even using service differentiation and, finally, simulates and evaluates the compliance with the established rules, considering a non-discriminatory mapping of applications in different Traffic Classes. The results indicate that the AllocTC-Sharing behavior is appropriate and compatible with the imposed net neutrality rules